Long-term trajectories of hepatic and metabolic biomarkers after switching from tenofovir disoproxil fumarate to tenofovir alafenamide in antiretroviral therapy-experienced people with HIV with and without hepatic coinfection: Data from the ICONA cohort - Poliseno, Mariacristina; Caputo, Sergio Lo; Tavelli, Alessandro; Gagliardini, Roberta; Gazzola, Lidia; Saracino, Annalisa; Santantonio, Teresa Antonia; Squillace, Nicola; Puoti, Massimo; Mazzotta, Valentina; Antinori, Adndrea; d’Arminio Monforte, Antonella; et al. (International journal of infectious diseases, 2025)
•Hepatic injury markers declined over 2 years after switching from tenofovir disoproxil fumarate to tenofovir alafenamide in people with HIV.•Reduction was stronger in patients with hepatitis B surface antigen+ and those with baseline chronic enzyme elevation.•Lipid parameters increased mainly in the first 6 months post-switch, then stabilized.•No significant lipid profile differences were reported by hepatitis B virus/hepatitis C virus coinfection status.•Except for low-density lipoprotein, hepatic/metabolic biomarker changes stayed normal, with limited clinical impact. Long-term effects of switching from tenofovir disoproxil fumarate (TDF) to tenofovir alafenamide (TAF) on hepatic, renal, and metabolic parameters remain poorly characterized, especially in people with HIV (PWH) and hepatitis B virus coinfection. We analyzed 24-month trajectories before and after the switch to TDF/TAF in antiretroviral therapy-experienced, virologically suppressed participants from the ICONA cohort, excluding those who started antiviral treatment or had detectable hepatitis C virus-RNA during the study period. Mean values at 18 (T–18) and 6 months (T–6) pre-switch, at switch, and 6, 12, and 24 months post-switch (T+6, T+12, T+24) were assessed using adjusted mixed linear models. At 6 months, alanine aminotransferase (ALT) decreased modestly by –3.05 (–6.42, 0.31) U/l, remaining stable at T+24; similar toother liver damage markers. In participants with chronic liver enzyme elevation, ALT reductions were more marked (–20.5 to –22.6 U/l from T+6 to T+24). Total cholesterol, low-density lipoprotein cholesterol (LDL-Chol), and triglycerides increased by 14.46, 10.70, and 11.56 mg/dl, respectively, at T+6, and then stabilized thereafter. PWH with baseline LDL-Chol <100 mg/dl showed larger LDL increases. Compared with HIV-monoinfected individuals, hepatitis B surface antigen+ individuals had higher ALT and lower estimated glomerular filtration rate on TDF; differences attenuated after switching to TAF (P <0.001 and P = 0.002). No lipid trajectory differences emerged by coinfection status. Greater hepatic improvement was noticed after TDF-to-TAF switch in PWH with hepatitis B virus coinfection, with no differences in lipid increases compared with monoinfected patients.